(untitled) (Eurasian Scientific Herald, 2023)
The article deals with the issues of modern accounting of intangible assets in accordance with national accounting standards and international financial reporting standards in Uzbekistan. A comparison was made between IAS- 38 and NAS-7 "Intangible Assets", discrepancies were identified and some measures were proposed to accelerate the introduction of international standards into national accounting practice.